Profile of Ankle Sprain Patients at Pusdokkes Polri Bhayangkara Tertiary Hospital - Yusticia Valen Pratidina; Basuki supartono (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2025)
Background: Ankle sprain is a musculoskeletal injury with the highest incidence rate in the world. Risk factors for ankle sprain are age, gender, sport, anatomical abnormalities, and body mass index (BMI). There is still contradiction as to whether gender is a risk factor for ankle sprain. Furthermore, there has been no research on ankle sprain regarding members of the Police Force as a risk factor. Objective: This research aims to determine the relationship between patient profile and acute ankle sprain at Pusdokkes Polri Bhayangkara Tertiary Hospital. Methods: This study took 124 research subjects, with consecutive sampling analysis, was an observational analytic study with a cross sectional research design involving patients diagnosed with ankle sprain in 2022 – 2023 at Pusdokkes Polri Bhayangkara Tertiary Hospital who met the inclusion and exclusion criteria. Result: As many as 79% of the subjects were aged 19 – 44 years (p=0.333). It was found that 52.4% of the subjects were male (p=0.944). As many as 46% of the subjects were members of the Police Force (p=0.181). Conclusion: Age, gender, and occupation had no significant association with the incidence of acute ankle sprain in this research. Male police officers aged 45 – 59 years have a higher risk of experiencing acute ankle sprain. The implication of this study is to prevent at-risk groups and/or ankle sprain patients.